PENGEMBANGAN BAHAN AJAR MENGGUNAKAN APLIKASI FLIP PDF CORPORATE PADA PEMBELAJARAN IPAS DI KELAS IV SEKOLAH DASAR - Aulia, Nurul; Akmal, Atika Ulya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was conducted due to the minimal use of IT-based teaching materials that are relevant to current developments, as well as the lack of variety in learning media. This research uses a Research and Development (R&D) approach by applying the ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation and Evaluation. With an average learning media validity of 92.7%, specific material validity 90%, language validity 96%, and media validity 92.1%, the final output is considered quite valid. With averages of 95% and 96.6% for teacher and student responses, respectively, the effectiveness category results yielded an average of 92.2% for effectiveness results. Therefore, it can be said that the use of Flip PDF Corporate teaching materials in science and science learning in elementary schools for class IV has been proven to be valid, practical and effective teaching materials.